Lymphoma-like monoclonal B cell lymphocytosis in a patient population: biology, natural evolution, and differences from CLL-like clones - Vander Meeren, Sam; Heyrman, Bert; Renmans, Wim; Bakkus, Marleen; Maes, Brigitte; De Raeve, Hendrik; Schots, Rik; Jochmans, Kristin (Annals of hematology, 2018)
High-count monoclonal B cell lymphocytosis (MBL) with a chronic lymphocytic leukemia (CLL) phenotype is a well-known entity, featuring 1–4% annual risk of progression towards CLL requiring treatment. Lymphoma-like MBL (L-MBL), on the other hand, remains poorly defined and data regarding outcome are lacking. We retrospectively evaluated 33 L-MBL cases within our hospital population and compared them to 95 subjects with CLL-like MBL (C-MBL). Diagnoses of L-MBL were based on asymptomatic B cell clones with Matutes score < 3, B cells < 5.0 × 10 3 /μl, and negative computerized tomography scans. We found that median B cell counts were considerably lower compared to C-MBL (0.6 vs 2.3 × 10 3 /μl) and remained stable over time. Based on immunophenotyping and immunogenetic profiling, most L-MBL clones did not correspond to known lymphoma entities. A strikingly high occurrence of paraproteinemia (48%), hypogammaglobulinemia (45%), and biclonality (21%) was seen; these incidences being significantly higher than in C-MBL (17, 21, and 5%, respectively). Unrelated monoclonal gammopathy of undetermined significance was a frequent feature, as the light chain type of 5/12 paraproteins detected was different from the clonal surface immunoglobulin. After 46-month median follow-up, 2/24 patients (8%) had progressed towards indolent lymphoma requiring no treatment. In contrast, 41% of C-MBL cases evolved to CLL and 17% required treatment. We conclude that clinical L-MBL is characterized by pronounced immune dysregulation and very slow or absent progression, clearly separating it from its CLL-like counterpart.